Penjadwalan Pembangkit Termal dengan Improved Lagrange Relaxation pada Sistem Jamali - 500 kV - inas sunaryanti ningsih; Hadi Suyono; Wijono Wijono (Fakultas Teknik, Universitas Brawijaya, 2017)
Unit Commitment (UC) is a problem to schedule generating units in a power system economically meeting the requirements of load demand and spinning reserve. Up to now several methods have been applied to solve this problem. Among those methods Lagrange Relaxation (LR) seems to be the most suitable one. However, this method may suffer from numerical convergence problem. This paper proposes a new method for solving UC problem. The proposed method uses Evolutionary Programming (EP) to update Lagrange multipliers and improves the performance of LR method. Simulation results show that the proposed method can provide a better solution compared with another methods.